Meningkatkan Hasil Belajar Siswa melalui Metode Pemberian Tugas dalam Mata Pelajaran PAK dan Budi Pekerti - Ni Ketut Nurhayani (Jurnal Kreatif Online, 2021)
The low learning outcomes of students in PAK and Budi Pekerti subjects in class VIII of SMP Negeri 6 Palu and the lecture teaching methods that are still used by teachers are the background of this research. The purpose of this study was to improve the learning outcomes of class VIII students of SMP Negeri 6 Palu through the assignment method. This type of research is classroom action research which consists of 2 cycles, each of which follows the stages of planning, implementing, observing and reflecting. The subjects of this study were students of class VIII SMP Negeri 6 Palu, totaling 20 students. The data collection technique used in this research is the learning outcomes test technique. Based on the research results that have been described previously, through learning improvement activities, it can be concluded that the use of the assignment method in learning PAK and good manners in class VIII SMP Negeri 6 Palu can improve student learning outcomes. The increase in student learning outcomes is evidenced by the percentage value of student learning completeness in cycle I and cycle II. In the first cycle of students who completed 12 people with a percentage of 60% completeness, increased in the second cycle with the number of students who completed 19 people with a percentage of 95%.